2021
DOI: 10.18608/jla.2021.7153
|View full text |Cite
|
Sign up to set email alerts
|

Using Innovative Methods to Explore the Potential of an Alerting Dashboard for Science Inquiry

Abstract: Educational technologies, such as teacher dashboards, are being developed to support teachers’ instruction and students’ learning. Specifically, dashboards support teachers in providing the just-in-time instruction needed by students in complex contexts such as science inquiry. In this study, we used the Inq-Blotter teacher-alerting dashboard to investigate whether teacher support elicited by the technology influenced students’ inquiry performance in a science intelligent tutoring system, Inq-ITS. Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Students' engagement in online social reading and discussion spaces in WiREAD fosters greater self-awareness, reflective, and self-regulatory learning dispositions (Tan et al, 2017). Additionally, a majority of students have shown significant improvement in their science inquiry practices using Inq-Blotter with teachers' guidelines (Dickler et al, 2021). The results also indicate that students immersed in learning analytics enhanced-technology settings have shown significant progress in arithmetic skills compared to those still taught in the paper & pencil setting (Molenaar et al, 2017).…”
Section: Impacts On Studentsmentioning
confidence: 96%
See 1 more Smart Citation
“…Students' engagement in online social reading and discussion spaces in WiREAD fosters greater self-awareness, reflective, and self-regulatory learning dispositions (Tan et al, 2017). Additionally, a majority of students have shown significant improvement in their science inquiry practices using Inq-Blotter with teachers' guidelines (Dickler et al, 2021). The results also indicate that students immersed in learning analytics enhanced-technology settings have shown significant progress in arithmetic skills compared to those still taught in the paper & pencil setting (Molenaar et al, 2017).…”
Section: Impacts On Studentsmentioning
confidence: 96%
“…It is also suggested that using learning analytics dashboards affects how teachers provide feedback concerning the type of feedback provided and how different types of feedback are channeled to students (Knoop-van Campen et al, 2021). Furthermore, alerting dashboard could inform teacher support of students' science inquiry practice competencies and the value of in-depth analyses of the implementation of new technological genres in classrooms (Dickler et al, 2021).…”
Section: Teachersmentioning
confidence: 99%
“…2.1 Design for human-AI complementarity ADS are increasingly used to support human work across a range of contexts, including education [2,13,23], healthcare [32,44,48], social work [8,34,41], and criminal justice [1,19,29]. Such systems seek to improve decision quality by leveraging the complementary skills of humans and AI systems.…”
Section: Background and Related Workmentioning
confidence: 99%
“…AI-based decision support tools (ADS) are being used to augment human decision-making across a growing range of domains-from predictive risk models used to augment decision-making in public services [11,25,27,34,41], to AI-based teacher support tools used in K-12 education [2,7,13,23,40], to clinical decision support tools used in healthcare [32,38,44,47,48]. The sociotechnical design of these systems often relies, whether implicitly or explicitly, on the potential for human-AI complementarity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, this year's articles mobilize LA to address several problems, including the lack of learning reflection among adolescents (Cloude et al, 2021), a need for students to read and respond effectively to different collaborative situations (Worsley et al, 2021), and the ways that confusion can impede students' metacognition (Zhang et al, 2021). We also see increased interest in tackling the challenges of more open-ended (Emara et al, 2021) and inquiry-based learning environments (Dickler et al, 2021;Rodríguez-Triana et al, 2021). Part of "closing the loop" continues to be methodological innovation and conceptual development.…”
Section: Problems Solutions and Impact In The Jla Papers Of 2021mentioning
confidence: 99%